Low grade endometrial stromal sarcoma in pregnancy: A case in support of safe abortion access - Rachel L. Furuya; David L. Eisenberg; Diana L. Gray; Vincent M. Mellnick; Premal H. Thaker (Elsevier, 2023)
Background: Endometrial stromal sarcoma (ESS) is extremely rare in pregnancy. It shares clinical and imaging features with more common pregnancy findings such as leiomyoma and molar gestations, which makes diagnosis challenging. Case: A 36-year-old patient presented at 8 weeks and 1 day gestation for vaginal bleeding. An intrauterine pregnancy with an appropriately sized embryo with heart motion and a 9.5 cm complex uterine mass was found on ultrasound. MRI showed an 11.4 cm cystic mass with nodular septations causing mass effect on the endometrial cavity. After extensive counseling, the patient underwent a gravid abdominal hysterectomy and bilateral salpingectomy. Final pathology showed low grade ESS. Conclusion: This case highlights the importance of evaluating suspicious uterine masses in pregnancy and the necessity for safe abortion access.